2008
DOI: 10.1038/eye.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic vitreous disruption

Abstract: Enzymatic vitreous disruption refers to cleaving the vitreoretinal junction by enzymatic means, thereby inducing posterior vitreous detachment (PVD) and liquefaction of the vitreous gel. Several enzymes have been proposed in this respect, including chondroitinase, hyaluronidase, dispase, and plasmin. In an experimental setting, chondroitinase induced PVD and was helpful in removing epiretinal membranes but no further data have been reported yet.Hyaluronidase liquefies the vitreous as demonstrated in a phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 34 publications
0
16
0
3
Order By: Relevance
“…Ocriplasmin is given as an intravitreal injection, and is designed to dissolve the vitreous and loosen its adhesion to the internal limiting membrane. [14][15][16][17] A recent, large, double-masked, randomized controlled trial reported that vitreomacular adhesion was fully resolved in 26.5% of cases after a single intravitreal injection of 125 mg of ocriplasmin. 16 Other authors have reported pilot data using an intravitreal gas injection to mechanically release VMT, with 40% to 55% response by 1 month.…”
mentioning
confidence: 99%
“…Ocriplasmin is given as an intravitreal injection, and is designed to dissolve the vitreous and loosen its adhesion to the internal limiting membrane. [14][15][16][17] A recent, large, double-masked, randomized controlled trial reported that vitreomacular adhesion was fully resolved in 26.5% of cases after a single intravitreal injection of 125 mg of ocriplasmin. 16 Other authors have reported pilot data using an intravitreal gas injection to mechanically release VMT, with 40% to 55% response by 1 month.…”
mentioning
confidence: 99%
“…Indeed, clinical applications of pharmacologic vitreolysis can be broadly grouped into two categories based on utilization model: pharmacology-assisted vitrectomy and pharmacologic PVD induction. In the former model, a pharmacologic agent administered preoperatively acts to either induce vitreous liquefaction, allowing for more rapid vitreous removal, or weaken the vitreorentinal adhesion, allowing for greater ease of mechanical PVD induction with a cleaner vitreoretinal separation 15,6467. More rapid vitreous removal translates into shorter surgical times15,25,68 and possibly an increased ability to employ smaller gauge instrumentation,69,70 which are associated with reduced postoperative recovery times 71,72.…”
Section: Indications For Pharmacologic Vitreolysismentioning
confidence: 99%
“…The mechanism of PVD is not yet fully understood, but over the last 2 decades, many studies have contributed to a better comprehension of the molecular organization, structure, and physiology of the vitreous, promoting the development of pharmacologic vitreolytics 28,29,31. The connection between cortical vitreous collagen with the ILM surface is believed to be mediated by some form of extracellular matrix “glue,” including the proteins laminin and fibronectin 1,28,29,4850.…”
Section: Resultsmentioning
confidence: 99%